Uygurca Altun Yaruk’a ait 50 belge - Küçük, Yahya (My University, 2003)
Bu çalışmada, Uygurca Altun Yaruk adlı esere ait 50 adet belgenin transliterasyonu ve transkripsiyonu bulunmaktadır. Eser, Mahayana Budizmine ait bir sutra kitabıdır. Buda'nın vaazlarını içerir. Eserin aslı Sanskritçedir. Sanskritçeden Çinceye, Çinceden de ŞIÑKO ŞELİ TUTUÑ tarafından Uygurcaya çevrilmiştir. Eserin en büyük nüshası Petersburg'da bulunmaktadır. İncelenen belgeler, Berlin-Brandenburg Bilimler Akademisi Turfan Koleksiyonu'nda saklanmaktadır. Çalışma; GİRİŞ, METİN, DİZİN ve TIPKIBASIM olmak üzere dört bölümden oluşmaktadır. Çalışmada belgelerin transliterasyonu ve transkripsiyonu yapıldı. Her bir belgenin, eserin RADLOFF-MALOV yayınındaki yerleri gösterildi. Ayrıca bütün kelimelerin dizini verildi. Çalışmanın sonuna belgelerin fotoğrafları eklendi. Eski Türkçe, Uygurca, Altun Yaruk, Suvarnaprabhasa, Şıñko Şeli Tutuñ, Budizm, Turfan

This work is based on the translation and transcription of fifty documents of Altun Yaruk in Uygur language. The Altun Yaruk is a sutra book of the Mahayana Buddhism and it includes Buddha's preaches. It is originally in Sanskrit. It was first translated into the Chinese and then from Chinese to Uighur language by ŞIÑKO ŞELİ TUTUÑ. The most complete copy of the work is said to be preserved in the Asian Museum in Petersburg. However, these fragments edited in this work are kept under protection among the Turfan collection in Berlin-Brandenburg Academy of Science. This study consists of four sections; Introduction, Text, Index, and Facsimile. This study includes transliteration and transcription of the fragments. Each fragment's place is located within the publication of RADLOFF-MALOV. All words were listed in alphabetic order. Photos of the fragments were also annexed to this study. Key words: Altun Yaruk (Golden Light), Turkic language, the Old Turkic, Uighur language, Suvarnaprabhasa, ŞIÑKO ŞELİ TUTUÑ, Buddhism, Turfan
Keywords: Uygur Dili